Radiation effect on MHD free-convection flow of a gas at a stretching surface with a uniform free stream - Ahmed Y. Ghaly; Elsayed M. E. Elbarbary (Journal of Applied Mathematics)
We investigate the problem of free convection heat transfer near an isothermal stretching sheet. This has been done under the simultaneous action of buoyancy, radiation, and transverse magnetic field. The governing equations are solved by the shooting method. The velocity and temperature functions are represented graphically for various values of the flow parameters: radiation parameter F, free convection parameter Gr, magnetic parameter M, Prandtl number Pr, and the parameter of relative difference between the temperature of the sheet, and the temperature far away from the sheet r. The effects of the radiation and magnetic field parameters on the shear stress and heat flux are discussed.